Degeneration of the vestibular nerve in unilateral Meniere's disease evaluated by galvanic vestibular-evoked myogenic potentials. Issue 9 (September 2017) - Chang, Chih-Ming; Young, Yi-Ho; Jaw, Fu-Shan; Wang, Chi-Te; Cheng, Po-Wen
Highlights: Meniere's retrolabyrinthine degeneration was assessed electrophysiologically. The impairment of otolithic organs was more than that of vestibular afferents. Meniere's disease duration positively correlated with stage and abnormal GVS-VEMP. Abstract: Objective: The staging system of Meniere's disease utilizes audiograms to probe cochlear dysfunction. We explored the addition of galvanic vestibular-evoked myogenic potentials (VEMP) to further explore vestibular function. Methods: Seventy patients with unilateral Meniere's disease were enrolled in this study. Within 2 weeks of diagnosis, all subjects underwent pure tone audiometry, cervical and ocular VEMP, and caloric test. The prevalence of abnormal tests and the VEMP characteristic parameters such as latencies and amplitudes were analyzed. Results: In affected ears, the abnormal rate of acoustic cVEMPs, galvanic cVEMPs, vibratory oVEMPs and galvanic oVEMPs was 37%, 17%, 20%, and 9%, respectively. No significant differences existed in VEMP latencies and amplitudes between affected ears and unaffected ears. Conclusions: The impairment of otolithic organs was found to be more than that of vestibular afferents. The deterioration of the saccule was more than that of the utricle, whereas retrolabyrinthine degeneration of sacculo-collic reflex and vestibulo-ocular reflex was similar. Significance: This study is the first to use an electrophysiological test to evaluate the retrolabyrinthine function of patients with unilateral Meniere's disease.